2007
DOI: 10.1073/pnas.0608422104
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced unfolding triggers adhesion of von Willebrand factor fibers

Abstract: von Willebrand factor (VWF), a protein present in our circulatory system, is necessary to stop bleeding under high shear-stress conditions as found in small blood vessels. The results presented here help unravel how an increase in hydrodynamic shear stress activates VWF's adhesion potential, leading to the counterintuitive phenomena of enhanced adsorption rate under strong shear conditions. Using a microfluidic device, we were able to mimic a wide range of bloodflow conditions and directly visualize the confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
777
5
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(820 citation statements)
references
References 23 publications
36
777
5
2
Order By: Relevance
“…61 Recently, fluorescence microscopy has been used to directly visualize individual fluorescently labeled vWF multimers under hydrodynamic stress in a microfluidic device. 42 vWF was fluorescently labeled with Alexa fluor 488, which was attached to the primary amines of the glycoprotein using tetrafluorophenyl ester. It was found that shear rates greater than 1000 s 21 triggered a reversible stretching of vWF in solution.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…61 Recently, fluorescence microscopy has been used to directly visualize individual fluorescently labeled vWF multimers under hydrodynamic stress in a microfluidic device. 42 vWF was fluorescently labeled with Alexa fluor 488, which was attached to the primary amines of the glycoprotein using tetrafluorophenyl ester. It was found that shear rates greater than 1000 s 21 triggered a reversible stretching of vWF in solution.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%
“…45 More importantly, the results 41 contradict the observed abrupt stretching of vWF ([20,000 kDa) in a microfluidic device at a threshold shear rate of 10 3 s 21 . 42 Clearly, the larger, more complex vWF would be expected to be more susceptible to shear stress relative to cytochrome c. However, it is noteworthy that specific conformational characteristics such as a-helix and b-sheet composition, and intra-molecular interactions (e.g., hydrophobic, electrostatic) and covalent bonds (e.g., disulfide), would be an important determinant of protein stability.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that this behaviour cannot be sustained indefinitely, and for extremely high shear rates one expects flow-induced dissolution of the aggregates. The enhancement in thrombus formation is particularly true in the presence of vWF, and it has been shown that the formation of the plug can be driven purely by flow in a reversible fashion [16][17][18] . Such behaviour is completely contrary to our intuition based on the fact that we typically use strong flows to disintegrate or dissolve matter, and thus the clotting scenario in which flow controls the reversible assembly of complex composites (with presumably tailored properties) represents a completely new aggregation paradigm that cannot be understood in terms of purely diffusion-limited and/or reaction-limited aggregation concepts.…”
mentioning
confidence: 99%
“…Beside inducing the binding to GpIb or to collagen surface, "activated" VWF was demonstrated to self-aggregate [13,31]. However, the data on molecular dimensions of VWF were obtained on the protein studied as a function of shear rate (up to >5000 sec -1 ) in a viscometer and successively transferred in a light…”
Section: Accepted M Manuscriptmentioning
confidence: 99%